Synergistic use of iron nanofertilizers and biotic elicitors to induce defensive volatile organic compound emissions from Brassica napus - Dariusz Piesik; Anna Wenda-Piesik; Jacek Łyczko; Grzegorz Lemańczyk; Jan Bocianowski; Magdalena Piesik (Journal of Plant Protection Research)
In light of the increasing world’s population and progressing climate changes, novel visions for agricultural practices are needed. In recent years nanofertilizers and elicitors have been investigated as methods to provide improved crop yield and quality. The potential of foliar application of iron nanofertilizers, elicitors (methyl jasmonate (MeJA) or methyl salicylate (MeSa)) and their combinations on the emission of volatile organic compounds (VOCs), have been evaluated for Brassica napus. The combined application of nanofertilizers and elicitors was found to result in an increase of VOC emissions by B. napus in comparison to their individual usage. The highest VOC emissions were observed at the time point 24 hours after the application of a 10 μg · ml–1 concentration of nanofertilizers and MeJa. To our knowledge, this is the first time that combinations of nanofertilizers and elicitors have been applied to plants to determine their response on the emission of plant defense volatiles.